Knowledge of Children on Harmful Traditional Practices, the Types and Regulations in Ghana - Sylvester Kyei‐Gyamfi; Frank Kyei‐Arthur; Kwami Sefa‐Kayi; Emmanuel Yeboah‐Djan; Robert Kwame Degraft Agyarko; Evans Sakyi‐Boadu; Afisah Zakariah (Reproductive, Female and Child Health)
ABSTRACT Background The paper aimed to examine children's awareness of harmful traditional practices (HTPs), the various types they are familiar with, the reasons for their persistence, and the effectiveness of national responses. Methods This study is a secondary analysis of both quantitative and qualitative data obtained from the Ministry of Gender, Children, and Social Protection, collected between April and October 2018. Descriptive statistics were utilized to analyze the quantitative data, while thematic analysis was applied to the qualitative data. The quantitative data set included 5,024 children aged 8 to 17, with males constituting 51.1% and females 49.9%. The qualitative component consisted of 10 focus group discussions and 50 key informant interviews. Results Overall, 88% of children were aware of HTPs that have an impact on them. HTPs identified by the respondents were early marriage, nutritional taboos, gender chores, female genital mutilation and menstrual taboos. The persistence of HTPs was attributed to ignorance, poverty, deeply rooted immersions in adherent cultures, and poor national and community regulations. Conclusion HTPs are widespread in Ghana, highlighting the need for policymakers to strengthen interventions and enforce policies enacted to address HTPs.